Philippine medical thesaurus on psychiatry and psychology behavioral discipline and activities and mental disorders in Bikol - Arevalo, Jeremy R. (2005)
This mini-thesaurus translated terms from the Psychology and Psychiatry facet of the Medical Subject Headings and used Bikol as the target language. Terms were translated using the top-down approach as a framework of domain analysis, which is based on deductive methods in generating systems. Terms were gathered from existing implementations, the Medical Subject Headings (MeSH) in particular. Terms were then translated using a list of ranked translation tools and supplementary materials. Experts' advices were sought on how the translated terms are written and pronounced. They were also consulted to clarify the meaning of the terms. User surveys were done through informant work. Analysis and methods involved term analysis and lexicographical work.